Survival prediction in patients with chronic obstructive pulmonary disease following a pulmonary rehabilitation programme in Hong Kong - Cherry WL Lau; Thomas Mok; William WN Ko; Bobby HP Ng; Irene HL Chan; Teresa TS Tsui; SO Ling; HY Kwan; YN Poon; CW Yim; PY Yau (SAGE Publishing, 2019)
Background and objective Pulmonary rehabilitation programme (PRP) is an important component in the management of chronic obstructive pulmonary disease (COPD). However, to date so far there has been limited literature on the survival outcomes of patients with COPD after a PRP in Hong Kong. This study aimed to investigate the outcomes of a pulmonary rehabilitation programme on the survival rates of a retrospective cohort of patients with COPD. Methods This was a retrospective study that included subjects who participated in the PRP in a rehabilitation hospital from the year 2003 to 2015. A total of 431 patients with chronic obstructive pulmonary disease were identified from the electronic record system of the hospital. The dataset were split into two age groups for reporting and analysis using the mean age of 72 as the cut-off. Their median survival times were calculated using Kaplan-Meier analysis. Cox-proportional regression model was used to explore factors that predicted better survival. The most significant predictors were used as strata, and their respective effects on survival functions were analysed with Kaplan-Meier analysis again. Results The overall median survival of the cohort was 4.3 years. The median survival times of the younger patient group (aged <72) and the older patient group (aged ≥72) were 5.3 and 3.6 years, respectively. For the patients, aged <72 years old, Moser's Activities of Daily Living class and the pulmonary rehabilitation programme completion rate were the most significant survival predictors. For the patients aged ≥72 years old, Monitored Functional Task Evaluation score was the most significant survival predictor. Conclusion Moser's Activities of Daily Living class ≥2 and non-completion of PRP for younger group, low exercise capacity with Monitored Functional Task Evaluation score <17 for older group were identified as significant predictors of poor survival. The findings of this study helped identifying those patients with COPD who have the needs to be more intensively treated and closely monitored.